Synthesis of Phthalimides: A New Entry via TBAI-Catalyzed Intramolecular Cyclization of 2-(Hydroxymethyl)benzamides - Nagaraju, Kare; Rajesh, Nomula; Krishna, Palakodety Radha (SynOpen, 2018)
Herein we report an unprecedented metal-free TBAI/TBHP mediated C–N bond formation via intramolecular cyclization of 2-(hydroxymethyl)benzamides to furnish N-substituted phthalimides in excellent yields.
Keywords: phthalimide; intramolecular cyclization; transition-metal free; C–N bond formation; oxidation